The contribution to climate change of the organic versus conventional wheat farming: A case study on the carbon footprint of wholemeal bread production in Italy. (1st June 2017) - Chiriacò, Maria Vincenza; Grossi, Giampiero; Castaldi, Simona; Valentini, Riccardo
Abstract: Despite many studies in literature demonstrate the environmental sustainability of organic food, a debate is still open in the scientific community on the effect of organic farming on global warming and climate change mitigation. This paper aims to contribute to a more informed debate on the actual contribution to climate change in terms of GHG emissions of organic and conventional agriculture. For this purpose, the production process of an organic vs conventional wholemeal bread locally produced in central Italy by a small-medium bakery enterprise was compared and the carbon footprint (CF) was assessed by means of the life cycle assessment (LCA) methodology. We found that the CF of 1 kg of the conventional wholemeal bread was 24% less respect to the same organic bread, with 1, 18 and 1, 55 kg CO2 eq respectively. On the contrary, if the CF is assessed per unit of cultivated area (hectare), wheat organic cultivation showed a better performance in terms of GHG emissions than conventional by 60%, with 1, 15 and 2, 87 Mg CO2 eq ha −1 respectively. The higher CF per unit of organic product is due to the lower yield per unit of area cultivated with organic farming and to the consequent attribution to a smaller amount of products of the GHG emissions generated in the field phase of the life cycle. Whereas, the CF per hectare is higher when conventional practices are applied due to the higher use of raw materials (higher seed density, agrochemicals for fertilization and plant protection) respect to the same organic system. Results of the study demonstrate that organic farming for wheat cultivation in Italy is a low-carbon agriculture with a lower contribution to climate change in terms of GHG emissions per hectare respect to the conventional wheat cultivation, although implications of the reduced productivity and the consequent need of more cultivated land should be considered. However, more research is needed to better explore the potential of organic farming and to improve organic food production, optimizing the balance between the use of resources and yields, to ensure sufficient organic food supply at global level. A more comprehensive assessment of the actual GHG emitted in the atmosphere from both organic and conventional agricultural systems can be provided when the CF is assessed per unit of area, in addition to the CF per product unit, especially if also the carbon sink of the agrosystem is included. Highlights: Wheat cultivation is the hotspot in the life cycle of wholemeal bread production. CF is higher in organic products but lower per hectare of organic cultivated area. CF per unit of area provides more accurate assessment of the contribution to climate change. Organic farming for wheat cultivation in Italy is a low-carbon agriculture.